Simulation of Surface-Type Condensing Units for Heat Recovery from the Flue Gas with Air Heating; MATEC Web of Conferences; Vol. 91 : Smart Grids 2017 - Bespalov V. V. Viktor Vladimirovich (2017, 2017)
Title screen